PENYELIDIKAN KEBOCORAN PIPA BAWAH TANAH MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI WENNER-SCHLUMBERGER BERDASARKAN MODEL FISIS SKALA LABORATORIUM - Dodi Irwan Siregar; Juandi M; Mhd Edisar (Universitas Riau, 2018)
The research has been done using physical modeling of geoelectric configuration application of Wenner-Sclumberger to model the existence of underground pipe leakage. Modeling is done on a tub made of wood and glass which is filled with sand and clay as medium (host-rock) and the inclusion of leaked steel pipe, the first measurement model is done before the fluid flow into the leaking pipe, obtained the type of pipe resistance pattern 2310 Ωm at a depth of 25 cm from the sand surface with an error iteration of 9.5%. The second model is measured by flowing water into the leaking pipe obtained the pattern of resistance around the type of leakage where the leak is lower is between 6.49 - 55.9 Ωm lies in the horizontal range 12.5 - 20.5 cm and in the vertical range 10 - 45 cm from the sand surface with 25.8% error iteration. The third model is measured by flowing kerosene into leaking pipe can be seen clearly the pattern of distribution of resistance type around the leaky pipe is lower 12 - 71.3 Ωm lies in the horizontal range 11 - 19 cm and in the vertical range of 7-25 cm from the surface sand with 15.7% error iteration